MCM-41 impregnated with A zeolite precursor: Synthesis, characterization and tetracycline antibiotics removal from aqueous solution - Liu, Minmin (Elsevier, 2013)
In this paper, the MCM-41 has been modified by impregnation with zeolite A to prepare a kind of new adsorbent. The adsorption of TC from aqueous solutions onto modified MCM-41 has been studied. It was discovered that the adsorption capability of zeolite A modified MCM-41 (A-MCM-41) increased dramatically after modification. The modified MCM-41 was characterized by X-ray diffraction (XRD), nitrogen adsorption–desorption, Fourier Transform Infrared (FTIR) analysis, Transmission electron microscopy (TEM) images, and (29)Si and (27)Al Magic Angle Spinning Nuclear Magnetic Resonance (MAS NMR) spectra. The modified MCM-41 structure was still retained after impregnated with zeolite A but the surface area and pore diameter decreased due to pore blockage. The adsorption of TC on modified MCM-41 was discussed regarding various parameters such as pH, initial TC concentration, and the reaction time. The pH effects on TC adsorption indicated that the adsorbents had better adsorption performances in acidic and neutral conditions. The adsorption isotherms were fitted well by the Langmuir model. The adsorption kinetics was well described by both pseudo-second order equation and the intra-particle diffusion model. The adsorption behavior in a fixed-bed column system followed Thomas model. The adsorption behavior of TC was the chemical adsorption with an ion exchange process and electrostatic adsorption.